Uji Toksisitas Akut Limbah Cair Industri Tahu terhadap Ikan Patin (Pangasius sp.) (Acute Toxicity Test of Tofu Industrial Wastewater for Catfish (Pangasius sp.)) - Parlinggoman Sianturi; Miswar Budi Mulya; Riri Ezraneti (AQUACOASTMARINE, 2014)
Tofu industry is an industry that has grown rapidly in the society. Most of the tofu industry drain directly wastewater into the water. Changes in chemical and physic parameters of water will disrupt the organism life in it, one of the types of organisms is catfish (Pangasius sp.). Toxicity tests are used to determine the status of tofu industrial wastewater for the mortality rate of catfish. Therefore, the required value of Lethal Concentration (LC50) 96 hours which is the concentration that causes 50% of test animals died within 96 hours of exposure time. This study aims to determine the LC50 value of tofu industrial wastewater for the catfish and the concentration effect of tofu industrial wastewater for the mortality rate of catfish. The study was conducted from February until March 2014. Research procedures include preliminary testing, toxicity testing, and probit analysis. Toxicity testing of tofu industrial wastewater for catfish mortality rate in treatment concentration 2.29% kill 36.67% of the fish, 2.63% kill 46.67% of the fish, 3.02% kill 50.00% of the fish, 3.47% kill 56.67% of the fish, and 3.98 % kill 63.33% of the fish. The investigations showed results that LC50 value for 96 hours of tofu industrial wastewater to the catfish (Pangasius sp.) is 28839.93 ppm (2.88%).Keywords : Catfish, LC50, Tofu Industry, Wastewater